2020
DOI: 10.1051/e3sconf/202018002017
|View full text |Cite
|
Sign up to set email alerts
|

Gas yield variation in wood biomass co-current air gasification process – continuous operation

Abstract: The purpose of this work was to study the gas yield variation resulted from the cherry wood gasification with air using a lab-scale rotary kiln gasifier. The feedstock was continuously fed into the preheated reactor at 600°C, in co-current configuration, using atmospheric air as a gasifying agent. The results indicate the importance of oxidation reaction control, through the feeding flow rates of biomass and air and the reactants mixing rate. From the experiment, the hydrogen yields were about 2-4%, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been discovered in previous experiments that there is an ideal ER for biomass air/oxygen gasification. 19 In this study, it was found to be 0.2.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…It has been discovered in previous experiments that there is an ideal ER for biomass air/oxygen gasification. 19 In this study, it was found to be 0.2.…”
Section: Resultsmentioning
confidence: 47%
“…The effects of temperature, 8 pressure, 9 catalysts 10,11 , absorbents, 12 and reactor type 13–18 have been intensively studied. Research on different gasifying agents also has been carried out, such as air, 19 oxygen-enriched air, 20 oxygen, 21 steam, 22 CO 2 , 23 air–steam, 24 and oxygen–steam. 25 However, very limited studies were carried out to compare the effects of different gasifying agents on gasification performance.…”
Section: Introductionmentioning
confidence: 99%